House rental selection system using analytic hierarchy process (HRSS) / Siti Naemah Md Azlan - Md Azlan, Siti Naemah (2014)
Shelter is the one of the basic necessity to every people besides of cloth and food to live. A comfortable place is the most important thing for student to have a good environment to study. The problem is student difficult to find the right house such as the nearest distance with UiTM, lower rental fees and other criteria. In order to solve the problem, House Rental Selection System using Analytic Hierarchy Process (HRSS) is developing to ease the students to find house for renting that meet the best selection of house. The objective to developing the system is to identify the suitable criteria in selecting rental house among students. The other objective is to develop the system to ease the student to find the rent house and lastly to evaluate the usefulness of the system by the user. Selection of the house is made based on the criteria by implementing the AHP technique. AHP is a decision making model that aids decision making in our complex world. The criteria are identified from the Literature Review, interview and questionnaire which are rental fees, facility and house type. While the sub criteria for facility are furnish, convenience and the distance. The HRSS is developing based on Waterfall Model which comprises of Planning, Analysis, Design, Implementation and Documentation. To accomplish the study, questionnaire has been distribute among 30 students to get the feedback on the developed system. Based on the feedback from the respondents, the highest mean for construct usability is 4.5667, ease of use is 4.3667, content is 4.5, user interface is 4.333 and selection using AHP is 4.4667. Most of the students responded that the system was ease to use and would enable them to make a booking more efficient.